1987
DOI: 10.1128/jb.169.6.2828-2834.1987
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-fixing nodules induced by Agrobacterium tumefaciens harboring Rhizobium phaseoli plasmids

Abstract: Rhizobium phaseoli CFN299 forms nitrogen-fixing nodules in Phaseolus vulgaris (bean) The bacteria belonging to the genus Rhizobium form nitrogen-fixing nodules in the roots of legumes. Bacterial genes controlling nodulation, host range specificity, and nitrogen fixation have been located on large plasmids called Sym plasmids. One of the approaches used to evaluate the genetic informnation contained in plasmids has been the transfer of these plasmids to different Rhizobium species or to Agrobacterium tumefaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(73 citation statements)
references
References 31 publications
3
67
0
3
Order By: Relevance
“…Nitrogen yield of the plants was also increased up to 67%, when inoculated with the transconjugants rhizobial strains as compared with the un-inoculated controls. These are in agreement with Martinez et al (1987), who found that genetic transfer between Rhizobium species has led to increase nodulation and nodule fresh and dry weight in legumes along with increase the growth and development of host plant. Similarly Truchet et al (1991) illustrated that trans-conjugants resulted from di-parental mating showed significant increase above the mid-parents in nodule number and dry weight of shoot.…”
Section: Discussionsupporting
confidence: 80%
“…Nitrogen yield of the plants was also increased up to 67%, when inoculated with the transconjugants rhizobial strains as compared with the un-inoculated controls. These are in agreement with Martinez et al (1987), who found that genetic transfer between Rhizobium species has led to increase nodulation and nodule fresh and dry weight in legumes along with increase the growth and development of host plant. Similarly Truchet et al (1991) illustrated that trans-conjugants resulted from di-parental mating showed significant increase above the mid-parents in nodule number and dry weight of shoot.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, R. leguminosarum bv. phaseoli type II strains have a broad host range and single nitrogenase genes (5,29). The symbiotic plasmid analyzed is a complex structure containing a large amount of reiterated DNA sequences within the plasmid and with other regions of the genome as well, especially in other plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…biovar 1 (14,16,23,31). Nevertheless, the symbiotic plasmid of CIAT 899 can be expressed in an A. tumefaciens C58 genetic background (15), and this fact suggests a degree of phenotypic relatedness between these two strains. The metabolic properties of the R. galegae strains were closely related to those of Agrobactenum strains (cluster 4).…”
Section: Discussionmentioning
confidence: 99%